Working the Spaces of Power Activism, Neoliberalism and Gendered Labour - Newman, Janet (Bloomsbury Academic, 2012)
This book is available as open access through the Bloomsbury Open Access programme and is available on www.bloomsburycollections.com. This book highlights the way in which contemporary forms of governance, policy and politics have been reframed by women 'working the spaces of power'. It shows how they took activist commitments into their working lives, in the process negotiating the terrain of neoliberal governance. Their work generated new political movements, community initiatives, public policies, organizational logics and forms of 'knowledge work'. Newman draws on over 50 interviews with women from four generations to interrogate, develop and challenge existing approaches to understanding social and political change. In a postscript she traces ways in which the analysis might 'speak to the present' and offer resources for contemporary politics and practice.